PENGARUH DISIPLIN KERJA GURU TERHADAP DISIPLIN BELAJAR SISWA SEKOLAH DASAR - Iswan -; Indah Hadidah (Universitas Muria Kudus, 2019)
The purpose of this study are 1) knowing the application of the work discipline of teachers in SDN 02 Sawangan Depok, 2) knowing the application of student learning discipline in SDN 02 Sawangan Depok, and 3) knowing the effect of the teacher's work discipline on the learning discipline of fourth grade students in the SDN 02 Sawangan Depok.This research uses a quantitative approach. Data was collected by distributing questionnaires to 30 students as respondents. Test the validity and reliability of the questionnaire in this study using the Statistical Package for the Social Sciences (SPSS) program with type 21.00.The results showed that 1) based on the results of the rating scale analysis test obtained a questionnaire value of 1150 with intervals ranging from 1081-1440. This means that the application of the work discipline of teachers in SDN 02 Sawangan Depok in the category of